The Role of Land Deeds Official Certifier (Ppat) in Terms of Transfer of Land Rights Through Land Exchange in The Development of Educational Infrastructure - Maudina, Erika; Azzahra Dwi Rizki; Nurhasanah, Diva Ahda; Adriansyah, Anggi Pratiwi; Noor, Aslan (Magister Kenotariatan Universitas Pasundan, 2024)
An alternate this is used as a way of shifting land rights need to be provenby a deed drawn up by the performing Land Deed Maker, hereinafter abbreviated as PPAT. as a consequence there may be an absolute detail that must be fulfilled in moving land rights, particularly the Deed of transfer of Land Rights made via the PPAT. based totally on this, the researcher observed issues, namely (1) what's the role of the Land Deed authentic (PPAT) in moving land rights through exchange? And (2) What are the legal outcomes for the events who enter into an agreementto change land with ownership rights? This studies uses a normative juridical technique, by means of analysing both written and unwritten rules. The studies stage used is the literature stage. the information evaluation used is qualitative juridical. In conclusion, the Land Deed legit (PPAT) inside the case of transfer of land rights through land switch within the production of educational infrastructure centers can't be processed in order that it isn't in accordance with Article 37 paragraph (1) of government regulation No. 24 of 1997 regarding Land Registration and Article 2 of government regulation No. 37 of 1998 regarding guidelines on the location of Land Deed legit. The prison results of the land change agreement for the improvement of instructional infrastructure encompass disputes arising from errors in the deletion of land rights in SD 03 Pakintelan, Gunungpati District, Semarang town, Mangunsari Village